Evaluation of the accuracy of three design methods for reinforced piled embankments - Rebolledo, Juan Felix Rodriguez; Palmeira, Ennio Marques; Araújo, Gregório Luís Silva; Cunha, Juliana Araujo da; Filho, José Melchior (Frontiers in Built Environment, 2025)
The construction of road and railway embankments adheres to strict specifications, particularly regarding stability and limited settlements. Consequently, their foundations must be designed to ensure satisfactory stress redistribution, preserving the integrity of the structure to prevent failures and large deformations. In this context, both physical and numerical models can provide a detailed evaluation of soil response and load transfer. This study compares the predictions from two-dimensional Finite Element Method (FEM) numerical analysis with those from a large scale instrumented physical model. The instrumentation included load cells at the head of one of the piles and total stress cells at various depths. After validating the results, analyses were conducted to compare predictions from different standard design methods. The vertical stress applied to the pile caps, total stresses, and efficiencies predicted by each model were examined. The results indicated that the method which best predicted both the stress at the pile cap and the model’s efficiency was the concentric arches.